Competition And Real Activities Manipulation - Datta, Sudip; Iskandar-Datta, Mai; Singh, Vivek (Journal of Applied Business Research, 2019)
We enrich the research on income manipulation by establishing a link among companies’ price-setting control and the extent of real activities management. Examining three types of real activities management, the results reveal an interesting asymmetry in how companies employ income manipulation based on their pricing strength. We discover that companies with weaker price-setting clout employ larger manipulation of sales and production costs as a tool to manage income, while firms with more dominant pricing power prefer managing discretionary expenses.